1997
DOI: 10.1073/pnas.94.16.8575
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for clathrin in cytokinesis

Abstract: Using clathrin-minus Dictyostelium cells, we identified a novel requirement for clathrin during cytokinesis. In suspension culture, clathrin-minus cells failed to divide and became large and multinucleate. This cytokinesis deficiency was not attributable to a pleiotropic effect on the actomyosin cytoskeleton, since other cellular events driven by myosin II (e.g., cortical contraction and capping of concanavalin A receptors) remained intact in clathrin-minus cells. Examination of cells expressing myosin II tagg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 28 publications
3
83
0
Order By: Relevance
“…USA 95 (1998) 13655 furrow by accessory proteins that recognize the myosin II tail, and such proteins are worth searching for. Intriguingly, myosin II does not localize to the furrow region in clathrin heavy chain-null mutants of Dictyostelium (25). This observation might imply that myosin II transporters could be membranous elements, perhaps driven along microtubules by kinesin-like motors, as suggested by Vallee et al (26).…”
Section: Fig 2 Gfp-rlcmentioning
confidence: 50%
“…USA 95 (1998) 13655 furrow by accessory proteins that recognize the myosin II tail, and such proteins are worth searching for. Intriguingly, myosin II does not localize to the furrow region in clathrin heavy chain-null mutants of Dictyostelium (25). This observation might imply that myosin II transporters could be membranous elements, perhaps driven along microtubules by kinesin-like motors, as suggested by Vallee et al (26).…”
Section: Fig 2 Gfp-rlcmentioning
confidence: 50%
“…Several studies have indicated that actomyosin ring assembly and remodelling during cytokinesis is strictly dependent on membrane trafficking during furrowing. For example in Dictyostelium, clathrin-minus cells fail to assemble myosin II into a functional contractile ring and mutations in syntaxin1 disrupt actin organisation during furrow formation of Drosophila embryos (Niswonger and O'Halloran, 1997;Burgess et al, 1997). Interestingly, live analysis of fluorescent tagged vesicles and F-actin movement during cytokinesis of postcellurized Drosophila embryos has suggested a model in which actin and membrane are delivered as a unit to the invaginating furrows (Albertson et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Endolysosomal involvement in cytokinesis has been previously demonstrated; both copine A, a calcium-dependent membrane binding protein involved in endolysosomal membrane trafficking, 53 and clathrin-mediated membrane trafficking and processing of proteins are required for cytokinesis in Dictyostelium. 54 Endosomal sorting complex required for transport (ESCRT) components, originally found to be involved in endosomal sorting and multivesicular endosome biogenesis, have also been identified in cytokinesis control. 55 Abscission is known to be carried out by the combination of several events including vesicle trafficking, microtubule remodeling and membrane deformation.…”
Section: Discussionmentioning
confidence: 99%